Study on cutting intervals on biomass yield, nutritive value and their oxalate content of different high yielding napier (P. purpureum) cultivars (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The aim of the experiment was to determine the biomass yield, morphological characteristics and nutritive value of different high yielding Napier cultivars according their cutting intervals. This study mainly discussed about four Napier cultivars named BLRI-Napier-4, Wruk-Wona, Napier-Hybrid (Japan) and MarkEron. The cutting interval was 45 days. The  result showed significant difference (p